Therapeutic potential of adipose derived stromal cells for major skin inflammatory diseases - Galera, Marina Ramírez; Svalgaard, Jesper; Woetmann, Anders (Frontiers in Medicine, 2024)
Inflammatory skin diseases like psoriasis and atopic dermatitis are chronic inflammatory skin conditions continuously under investigation due to increased prevalence and lack of cure. Moreover, long-term treatments available are often associated with adverse effects and drug resistance. Consequently, there is a clear unmet need for new therapeutic approaches. One promising and cutting-edge treatment option is the use of adipose-derived mesenchymal stromal cells (AD-MSCs) due to its immunomodulatory and anti-inflammatory properties. Therefore, this mini review aims to highlight why adipose-derived mesenchymal stromal cells are a potential new treatment for these diseases by summarizing the pre-clinical and clinical studies investigated up to date and addressing current limitations and unresolved clinical questions from a dermatological and immunomodulatory point of view.